Association of oxidative balance scores with cardiovascular and all cause mortality in patients with asthma - Wei Zhao; Yiyuan Sun; Bohui Zhu (Scientific Reports)
Abstract Asthma poses significant societal costs, and a wholesome diet coupled with an energetic lifestyle might enhance postpartum results. Regrettably, empirical investigations into dietary and lifestyle aspects that amplify asthma risk remain scarce. The oxidative balance scores (OBS), quantifying oxidative stress from dietary elements and lifestyle parameters, lack a definitive link to overall and cardiovascular mortality among asthmatic individuals. Data sourced from NHANES (1999–2020) were utilized to investigate the correlation between the OBS index and all-cause and cardiovascular mortality among asthmatic patients. Rigor was maintained through the implementation of subgroup and sensitivity analyses to authenticate the findings. The study finally included 4,639 individuals with a mean age of 42.55 years and 43.46% males. Kaplan-Meier curves showed that asthmatics with lower OBS quartiles had a higher risk of all-cause and cardiovascular mortality. In the fully adjusted Model 2, the HR for all-cause mortality in the upper quartile of asthmatics in the OBS was 0.37 (95% CI: 0.26, 0.53), in contrast to the lower quartile of asthmatics. Cardiovascular disease mortality showed consistency (Q4, HR: 0.43, 95% CI: 0.19, 0.98). The association between the OBS index and both all-cause and cardiovascular mortality in asthma patients remained stable across different models and subgroup assessments. Restricted cubic spline curves showed that OBS was linearly associated with all-cause and cardiovascular mortality in asthmatics. A sensitivity analysis reinforced the negative correlation between the OBS index and mortality in asthma patients. The OBS index was negatively correlated with all-cause and cardiovascular mortality in patients with asthma, emphasizing the protective effect of an antioxidant diet and a healthy lifestyle in patients with asthma.